Comparison of transvaginal versus transumbilical retrieval technique of laparoscopically removed surgical specimens - Puri, Suman; Kaur, Manpreet; Aneja, Rashim; Ladher, Heena; Puri, Aneesha (International Journal of Research in Medical Sciences, 2023)
Background: Laparoscopy is a minimally invasive, safe, and acceptable technique for the removal of adnexal masses whereas specimen removal remains a big challenge due to the size and type of specimens. In this study, we have discussed the two different routes of specimen retrieval, transumbilical and transvaginal route. Methods: A prospective study was conducted on 34 women with adnexal mass who were admitted for laparoscopic removal of adnexal mass. Patients were randomized into two groups, Group A included 17 women who underwent transumbilical retrieval of specimens, and Group B included 17 patients who underwent transvaginal retrieval of specimens. Results: Basic demographic data were similar in both groups. None of our patients had intraoperative & postoperative complications. There was no significant difference in Specimen retrieval time, operative time, and blood loss. Two patients (N=2) in group A had spillage. Postoperative pain was significantly higher in group A and the cosmetic response was significantly higher in group B. Conclusions: Both transumbilical and transvaginal techniques of specimen retrieval in the laparoscopically resected specimen are safe, feasible, and easy, but the Transvaginal route has advantages over the transumbilical route because of better cosmesis and less postoperative pain.